ANAEROBIC DIGESTION OF MACROALGA Gracilaria sp. IN BATCH SYSTEM TO PRODUCE BIO-METHANE - Mujizat Kawaroe; Udin Hasanudin; . Krisye (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
This study aimed to determine the potential of bio-methane produced by Gracilaria sp. in a batch system. The experiment was conducted in batch system and it was initiated by acclimatization process (12 days) and ended methane production process (30 days). The results showed that biochemical properties of Gracilaria sp.  are carbohydrate 65.46 ± 0.58%, lignin 13.20 ± 2.23%, TOC (Total Organic Carbon) 33.39 ± 0.23%, Nitrogen 1.12 ± 0.01%, and C/N ratio 29.82. Acclimatization proceeded successfully and it was indicated by 62.7 L biogas of 4.025 L of substrate Gracilaria sp. produced within a pH range of 6.2 - 7.1. The batch method of anaerobic biodegradation showed that 4 kg of Gracilaria sp. can produced 131.1 L of biogas containing methane and 46.7 L or 11.6 L CH4 /kg.